2020
DOI: 10.21203/rs.3.rs-28729/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Dietary Diversity Practice and Associated Factors Among Pregnant Women Attending Anc in Kolfe Keranyo Sub City Health Center, Addis Ababa, Ethiopia.

Abstract: Background: Adequate and healthy diet during pregnancy is essential for the health of both mother and newborn. Dietary diversity is a proxy indicator of maternal nutrient adequacy. However, little is documented on dietary diversity among pregnant women. Objectives: This study was designed to assess the dietary diversity practice and associated factors among pregnant women attending ANC in health centers of the coffee keranyo sub city, Addis Ababa, Ethiopia. Methods: Institution based cross-sectional study was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 16 publications
1
3
0
Order By: Relevance
“…The findings of the present study are in agreement with several studies in Ethiopia that reported that women who had not yet started to consume an additional meal in pregnancy were less likely to have an adequate diversified diet compared to those who had started consuming additional meals (23,27). Another study in the east Gojjam zone of northwest Ethiopia and Hossana town, south Ethiopia found that increasing meal frequency improves women's dietary diversity (36,37). This might be because pregnant women who consume an additional meal per day have a greater chance of accessing different food groups.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The findings of the present study are in agreement with several studies in Ethiopia that reported that women who had not yet started to consume an additional meal in pregnancy were less likely to have an adequate diversified diet compared to those who had started consuming additional meals (23,27). Another study in the east Gojjam zone of northwest Ethiopia and Hossana town, south Ethiopia found that increasing meal frequency improves women's dietary diversity (36,37). This might be because pregnant women who consume an additional meal per day have a greater chance of accessing different food groups.…”
Section: Discussionsupporting
confidence: 92%
“…In this study, pregnant women who had attended antenatal care were more likely to consume diversified food groups compared with their counterparts. Other studies carried out in Ethiopia showed that pregnant women who had ANC visit were more likely to attain adequate dietary diversity than those who had not (36,37). Furthermore, a study conducted in Ghana investigated that frequent ANC attendance was a significant independent predictor of maternal dietary diversity (31).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, a study conducted in Addis Ababa, Ethiopia, showed that 31.3% of pregnant women exclude at least one food group from their meals due to traditional food taboos. 53 The current study revealed that the overall prevalence of undernutrition among the study participants was 23.9% (95% CI = 22.3, 25.5). According to World Health Organization (WHO) Prevalence cut-off values for public health significance, if the prevalence of undernutrition among adults, including pregnant women, is between 20% and 30%, then it is considered a high prevalence (serious situation), so based on the cut-off value, the study participants in our study area are in a serious situation.…”
Section: Discussionmentioning
confidence: 57%
“…Similarly, a study conducted in Addis Ababa, Ethiopia, showed that 31.3% of pregnant women exclude at least one food group from their meals due to traditional food taboos. 53…”
Section: Discussionmentioning
confidence: 99%